2022
DOI: 10.20944/preprints202211.0437.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Demystifying the Relationship Between River Discharge and Suspended Sediment Using Exploratory Analysis and Deep Neural Network Algorithms

Abstract: The dynamics of suspended sediment involves inherent non-linearity and complexity as a result of the presence of both spatial variability of the basin characteristics and temporal climatic patterns. As a result of this complexity, the conventional sediment rating curve (SRC) and other empirical methods produce inaccurate predictions. Deep neural networks (DNNs) have emerged as one of the advanced modeling techniques capable of addressing inherent non-linearity in hydrological processes over the last few decade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Long short-term memory is a type of recurrent neural network frequently used for time series forecasting and is often used when variables are dependent on the previous data in the series [51,52]. Long short-term memory has the ability to capture the long-term dependencies among the predictor and target variables [53,54]. Long short-term memory feedback connections are the principal component of processing and recalling long-term information; this is a unique feature which differentiates it from a traditional multilayer perceptron method.…”
Section: Long Short-term Memorymentioning
confidence: 99%
“…Long short-term memory is a type of recurrent neural network frequently used for time series forecasting and is often used when variables are dependent on the previous data in the series [51,52]. Long short-term memory has the ability to capture the long-term dependencies among the predictor and target variables [53,54]. Long short-term memory feedback connections are the principal component of processing and recalling long-term information; this is a unique feature which differentiates it from a traditional multilayer perceptron method.…”
Section: Long Short-term Memorymentioning
confidence: 99%
“…LSTM model have already been used as a very advanced model in the field of DL, e.g., speech recognition, natural language processing, automatic image captioning and machine translation [44,54,55]. However, only a few studies have applied Recurrent Neural Networks (RNNs) or LSTMs to forecast multivariate time series data in the field of water resource [56][57][58]. The objective of this research is to untangle the pattern of the temporal distribution and linkage among the aforementioned SW variables and perform predictive analysis on the using the previous observed data.…”
Section: Introductionmentioning
confidence: 99%
“…The LSTM model has been employed extensively in various fields of deep learning, such as speech recognition, natural language processing, automatic image captioning, and machine translation, showcasing its advanced capabilities [47,56,57]. In the realm of water resource forecasting, there have been limited instances where researchers have utilized Recurrent Neural Networks (RNNs) or LSTMs to predict multivariate time-series data [58][59][60]. The objective of this research is to untangle the pattern of the temporal distribution and the relation among the selected SW (surface water) variables for this study; as well as perform predictive analysis using observed data.…”
Section: Introductionmentioning
confidence: 99%